One American Perspective on the Rights of Accused: An Initial Survey of Miranda Rights in a Broader Context. (23rd May 2016) - Rogers, Richard; Sharf, Allyson J.; Clark, John W.; Drogin, Eric Y.; Winningham, Darby B.; Williams, Margot M.
Abstract : In the wake of countless police dramas, commonly held misperceptions endure that the American public knows both Miranda warnings and concomitant rights. Past research has tested public knowledge of Miranda per se, without evaluating additional misconceptions. The current investigation utilizes the European Union's much more all‐encompassing safeguards, as delineated in the EU's 2012 Directive and Letter of Rights. Besides knowledge of Miranda, the advisability of these enhanced rights and protections was also assessed. In order to obtain a cross‐section of the community, 619 participants were recruited from actual jury pools. Interestingly, they believed that Miranda afforded arrestees many more protections than it actually does. In general, nearly all (>90%) agreed that the accused should be given accurate information (e.g., charges and alleged criminal acts) coupled with an absence of police deception. The potential implications of these findings are discussed as they relate to police practices and due process. Copyright © 2016 John Wiley & Sons, Ltd.